2012
DOI: 10.1353/csd.2012.0017
|View full text |Cite
|
Sign up to set email alerts
|

The Context of Creating Space: Assessing the Likelihood of College LGBT Center Presence

Abstract: LGBT (lesbian, gay, bisexual, and transgender) resource centers are campus spaces dedicated to the success of sexual minority students. However, only a small handful of American colleges and universities have such spaces. Political opportunity and resource mobilization theory can provide a useful framework for understanding what contextual factors contribute to the presence of these centers. Independent variables’ effects on the likelihood of a campus having an LGBT resource center are measured using logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 32 publications
6
63
0
Order By: Relevance
“…Given the potential for LGBT groups and non-discrimination statements to foster more inclusive environments, it would seem important to understand why schools adopt such groups and policies in the first place, especially on Christian campuses where LGBT students are arguably most vulnerable. Surprisingly, few scholars have examined the characteristics of LGBT-inclusive schools, but articles by Fetner and Kush (2008) on the emergence of Gay-Straight Alliances (GSAs) in U.S. high schools, Fine (2012) on the presence of LGBT resource centers in U.S. colleges and universities, and Kane (2013a) on the presence of GSAs at North Carolina colleges and universities offer a few plausible explanations that may extend to the adoption of LGBT groups and non-discrimination policies at Christian colleges and universities.…”
Section: Previous Literature On School Approval Of Lgbt Groups and Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Given the potential for LGBT groups and non-discrimination statements to foster more inclusive environments, it would seem important to understand why schools adopt such groups and policies in the first place, especially on Christian campuses where LGBT students are arguably most vulnerable. Surprisingly, few scholars have examined the characteristics of LGBT-inclusive schools, but articles by Fetner and Kush (2008) on the emergence of Gay-Straight Alliances (GSAs) in U.S. high schools, Fine (2012) on the presence of LGBT resource centers in U.S. colleges and universities, and Kane (2013a) on the presence of GSAs at North Carolina colleges and universities offer a few plausible explanations that may extend to the adoption of LGBT groups and non-discrimination policies at Christian colleges and universities.…”
Section: Previous Literature On School Approval Of Lgbt Groups and Nomentioning
confidence: 99%
“…Scholarship on LGBT-inclusive schools has shown that schools' institutional characteristics, student body characteristics, and socio-political contexts play a role in the adoption of LGBT groups (Fetner and Kush 2008;Fine 2012;Kane 2013a). …”
mentioning
confidence: 99%
“…LGBT centers on college campuses are designed to provide critical resources for gender and sexual minority college students, yet their presence is closely linked to a college's liberal political leanings, which can limit their likelihood in more conservative regions (Fine, 2012). Furthermore, LGBT college students can establish stronger, more positive feelings surrounding their gender and sexual identities as a result of their involvement in LGBT-centered campus organizations (Renn, 2007).…”
Section: Runaway and Homeless Lgbt Youthmentioning
confidence: 99%
“…Fine (2012) LGBT centers are a major source of support for LGB students, organizing education, programing and support services for the community, including diversity training for students, staff and faculty.…”
Section: Lgbtq Resource Centersmentioning
confidence: 99%